Shadow education in Latin America: Assembling the jigsaw - Mark Bray; Alexandre Ventura (Revista Española de Pedagogía)
Shadow education is a widely used metaphor for private supplementary tutoring, i.e. instruction in academic subjects on a fee-charging basis outside school hours. The metaphor is used because much tutoring mimics schooling. Thus, as the curriculum changes in the schools, so it changes in the shadows; and as schooling grows, so does the shadow. Initially with particular prominence in East Asia, albeit with deep roots elsewhere, shadow education has expanded worldwide. The phenomenon has been mapped in Africa, Asia, Europe, the Mid- dle East and North America, but has received modest attention in Latin America. This article provides an overview of the phenomenon in the region using available data and stressing the need for further research. It presents global as well as Latin American contextual factors and drivers of demand before turning to data on the scale, nature and suppliers of shadow education. The assembled picture then permits commentary on educational and social impact, and on policy implications.